2019
DOI: 10.1111/bju.14800
|View full text |Cite
|
Sign up to set email alerts
|

Using prognosis to guide inclusion criteria, define standardised endpoints and stratify follow‐up in active surveillance for prostate cancer

Abstract: Objectives To test whether using disease prognosis can inform a rational approach to active surveillance (AS) for early prostate cancer. Patients and methods We previously developed the Cambridge Prognostics Groups (CPG) classification, a five‐tiered model that uses prostate‐specific antigen (PSA), Grade Group and Stage to predict cancer survival outcomes. We applied the CPG model to a UK and a Swedish prostate cancer cohort to test differences in prostate cancer mortality (PCM) in men managed conservatively o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Although previous work has also shown that baseline MRI lesion score and PSA-D are significant predictors of AS progression [15,16] and evaluation of baseline risk factors is a key in selecting patients for AS and in tailoring follow-up [17], this will not predict the time point when changes may occur, which is potentially offered by MRI-based PRECISE scoring as part of a follow-up programme. PRECISE scoring with a cut-off value of ≥ 4 had an AUC of 0.83 and overall accuracy of 86.8% in predicting AS progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous work has also shown that baseline MRI lesion score and PSA-D are significant predictors of AS progression [15,16] and evaluation of baseline risk factors is a key in selecting patients for AS and in tailoring follow-up [17], this will not predict the time point when changes may occur, which is potentially offered by MRI-based PRECISE scoring as part of a follow-up programme. PRECISE scoring with a cut-off value of ≥ 4 had an AUC of 0.83 and overall accuracy of 86.8% in predicting AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we employed a Likert scoring system rather than PI-RADS; however, PI-RADS scoring can only be used for baseline evaluation and cannot be used for the follow-up assessment of patients on AS [32], and outcome data in biopsy-naïve patients has shown Likert-based scoring to perform well [33][34][35]. Future prospective studies assessing the predictive value of PRECISE with standardized AS end-points are required to address these limitations [16].…”
Section: Discussionmentioning
confidence: 99%
“…The core differences between the CPG system and the traditional three-tiered systems are the subdivision of intermediate-risk disease into CPG2 with favourable features (Gleason score 3 + 4 or PSA 10-20) and CPG3 with unfavourable features (Gleason score 3 + 4 and PSA 10-20, or Gleason score 4 + 3) as well as the subdivision of high risk into CPG4 (one high-risk feature of Gleason score 8, PSA > 20 or T3) and CPG5 (more than one high-risk feature of Gleason score 9-10 or T4) ( Table 1) [3,5]. With this finer degree of granularity, the CPG classification is the first reported classification system of prostate cancer risk that incorporates recommendations of the International Society of Urological Pathology on the grading of prostate cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…For this latter group there remains understandable anxiety on the part of many clinicians in pursuing a non‐interventional approach. This is both a limitation and also a potential opportunity for AS practice to evolve, particularly in the light of modern monitoring tools and a better understanding of prognosis [2].…”
mentioning
confidence: 99%
“…Indeed, there is potential to repurpose other existing drugs in this early phase, not as curative agents, but rather as targeted short‐term cytotoxic strategies to reduce tumour burden and delay/abrogate the need for future radical therapy. This might be particularly attractive in those men on AS who are known to be at higher risk of progression [2, 7]. In such studies the ability to biopsy, molecularly profile and non‐invasively monitor tumours at the outset and during AS in ‘window trials’ is potentially unique in oncological trial design, alongside the ability to detect early non‐responders and rapid conversion to radical treatment.…”
mentioning
confidence: 99%